Specific Characteristics of Youth Social Group and its Place in Community Life - Sarvar Otamuratov (Periodica Journal, 2022)
This article analyses concepts of unorganized young people, passive young people and active young people and their role in society. The presented information defines scientific discoveries and their suitability. The author presented factors which can affect the increase of the numbers of active young people over the numbers of unorganized young people and also negative sides of passive young people. Besides that, this article suggests measures to consolidate efforts of the state organizations and non-state organizations in activations of unorganized and inactive young people and to involve them in a creative activity
Keywords: Unorganized Young People; Passive Young People; Active Young People